Peptide hydrolases of Antarctic krill, Euphausia superba - Osnes, Knut Kristian (Norwegian Institute of Technology, University of Trondheim, 1985)
Publication Title: Department of Biochemistry ISBN: 8272450119
Keywords: Antarktis; NARE 1978/79; Sørishavet; biokjemi; fiskeprodukter; krill; lyskreps; marin biologi; peptider

On the purification and characterization of three anionic, serine-type peptide hydrolases from antarctic krill, Euphausia Superba - Osnes, Knut Kristian; Mohr, Viggo (Comparative Biochemistry and Physiology Part B: Comparative Biochemistry, 1985)
1. Three enzymes effecting hydrolysis of TAME have been purified from E. superba using gel filtration, affinity chromatography and FPLC-anion exchange chromatography. 2. The enzymes had molecular weights of 30,000 (Enzyme I), and 31,000 (Enzymes II and III), respectively, as estimated from SDS-PAGE. 3. pH-optima of about 8.2 were observed for all three enzymes. 4. The enzymes were inhibited by phenyl methyl sulphonyl fluoride (PMSF), tosyl lysyl chloromethyl ketone (TLCK) and soybean trypsin inhibitor (SBTI), whereas tosyl phenyl chloromethyl ketone (TPCK) had no effect on the activity. 5. The enzymes were stable at neutral pH, and only slowly inactivated at highly alkaline pH. Low pH rapidly inactivated all three enzymes. 6. Enzyme I liberated amino acids from casein, whereas Enzymes II and III did not; the latter two being true endopeptidases which effected enhanced amino acid production from casein when mixed with Enzyme I.
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; Sørishavet; biokjemi; krill; marin biologi; plankton

Peptide hydrolases of Antartic krill, Euphausia superba - Osnes, Knut Kristian; Mohr, Viggo (Comparative Biochemistry and Physiology Part B: Comparative Biochemistry, 1985)
1. A survey has been made of the peptide hydrolase activities occurring in Antarctic krill, Euphausia superba. 2. A major protein hydrolyzing activity in the pH range of 6–8, and a minor activity at pH 3–4, were detected. 3. Temperature optima of approx. 50°C and 35–40°C, respectively were determined for the neutral and acid peptide hydrolases. 4. Trypsin-like activity, as well as carboxypeptidase A-, carboxypeptidase B-, and aminopeptidase activity were detected in extracts of krill. 5. Considerable variation in total hydrolase activity was observed in different catches of E. superba obtained from the same area. 6. The pattern of release of amino acids during autolytic breakdown of krill proteins was very similar in catches of krill exhibiting considerable differences with respect to total peptide hydrolase activity.
Keywords: Bouvetøya; NARE 1976/77; NARE 1978/79; Sørishavet; biokjemi; krill; marin biologi; plankton

The distribution of lipid in the tissues of Antarctic krill, Euphausia superba - Saether, Olav; Ellingsen, Trond E.; Mohr, Viggo (Comparative Biochemistry and Physiology Part B: Comparative Biochemistry, 1985)
1. The distribution of lipid in the tissues of Euphausia superba has been examined by histological and chemical methods. 2. The total lipid content of krill from different catches may vary considerably, and the variations are probably due both to differences in nutritional status and maturity of the roe of female krill. 3. Female krill contained about twice as much lipid as male krill from the same haul. 4. The roe is the dominating lipid depot in female krill; in both male and female krill lipid-rich areas are found along the digestive tract, between muscle bundles and beneath the exoskeleton. 5. Both the phosphoglyceride- and triacylglycerol content of body fractions of E. superba varied in proportion to the total lipid content, thus supporting the contention that both phosphoglycerides and triacylglycerols serve as depot lipids in this species of krill.
Keywords: Sørishavet; biokjemi; krill; marin biologi; plankton